ANALISIS NILAI TAMBAH PENGELOLAAN PISANG RAJA MENJADI KERIPIK PISANG DI IKM SAHRUL DESA RAMPADENDE KECAMATAN DOLO BARAT KABUPATEN SIGI - Koko Ferdiansyah; Dafina Howara; Moh Alfit Alaihi (Jurnal Pembangunan Agribisnis (Journal of Agribusiness Development), 2022)
Sahrul SMEs is an example of a real contribution to the industrial-based agriculture sector by processing banana king into chips to provide more selling value. The availability of abundant Banana king commodities makes Sahrul SMEs utilize these commodities as raw materials in food-based industrial activities. However, the price of some supporting materials used in processing banana king into banana chips is still relatively high and some processes use large costs. Because of this, there needs to be an analysis of income and the amount of added value on banana chips till business can develop and continue. This study aims to determine how much one-time production income and to find out the value added of banana chip products at Sahrul SMEs. This research was carried out at Sahrul SMEs, Rampadende Village Dolo Barat District Sigi Regency, in September-November 2019. The results showed that the income earned by Sahrul SMEs in one month of production was Rp.2,096,458, - value added analysis of Rp. 141,000 with a ratio of 0.64% of the raw materials used with a profit of Rp. 120,167 or 0.85% of every one banana bunch used.